Article Review: Editing genome of Toxoplasma gondii by CRISPR/Cas9 system - Musafer H. Al-Ardi (مجلة جامعة الانبار للعلوم الصرفة, 2020)
It is well known that finding out the genetic information of any organism helps in understanding how performs its metabolism, and knowing the extent of the effect that gene modification affects the performance of these functions. Many techniques have been used to editing genome of parasites such as Zinc fingers and Transcription activator-like effector nucleases (TALENs), But the development of clustered regularly interspaced short palindromic repeats/ CRISPR-associated (CRISPR Cas9) system created the quantum leap in this area, as this technique relies on identifying the portion to be modified using a guide from Guide RNAs (gRNA) that identifies this part very accurately. Not only that, but the enzyme present with it called CAS9 works as a molecular scissor to cut DNA at this part and allow the required modification.Since 2014, the date on which the first article about use CRISPR/Cas9 in the editing of Toxoplasma gondii genome was published, after that continued, developed new methods and protocols that facilitate the researchers work, we will attempt in this paper to review some of these major achievements.